The role of indirect external dialogue in the epic of zambilfirosh by feqiye teyran - Rasheed, Soleen; Othman, Nawzat (Humanities Journal of University of Zakho, 2023)
Since ancient times, dialogue has had a great impact on human life, as it contributes to strengthening relationships, exchanging ideas, and revealing secrets between people. Its importance is evident in most literary genres, especially in artistic techniques, where its role appears in it. According to this hypothesis, the literary text is built on the indirect external dialogue, and it is one of the dominant and prevalent genres in the epic text. The study is based on the assumption that the external, indirect dialogue plays a major role in the embodiment of the characters and the sequence of events in the epic "Zimbelfrosh" by (Fakih Al-Tayran). The research attempted to find out: Was the indirect dialogue in Zimbilfrosh Faqi Airan the reason for expressing the intellectual and emotional attitude, as well as the natural, psychological, and social dimensions of the characters? And to what extent does the indirect dialogue contribute to the development of events and the disclosure of secrets? This study, titled "The Role of Indirect External Dialogue in the Epic of Zambilfirosh by Feqiye Teyran," is an effort to illustrate the role of indirect external dialogue in the epic of Zambilfirosh. In the beginning, this study briefly discusses the history, usefulness, and role of dialogue. It later, studies the indirect dialogue in Zambilfirosh of Feqiye Teyran. In this research, the descriptive analytical method has been applied.